Penggunaan Teknologi Informasi dan Komunikasi (TIK) dalam Knowledge Sharing pada PT. Indonesia Villa Jaya Batam - Ummul Fitri Afifah (Politeknik Negeri Batam, 2019)
Knowledge management has been applied in various organizations. The implementation of knowledge management will not work if there is no process of knowledge sharing. Knowledge sharing is the key to an organization's success. To facilitate knowledge sharing, it can use information assistance. The existence of information technology can be an enabler in the process of knowledge sharing. PT. Indonesia Villa Jaya is a company of production field. This company is one of the companies that already did knowledge sharing activities. Knowledge sharing activities include routine meetings, training, watching together, and many other activities. Knowledge sharing activities in this company are also inseparable from the role of information technology. However, this time, the use of information technology in this company has not been maximized that there are still many complaints from employees regarding the use of information technology for knowledge sharing. This study aims to determine the description of the use of information technology for knowledge sharing. The information technology that will be discussed from this research are ICT tools, ICT infrastructure, and ICT know-how. This is a quantitative research. The population of this research is the employees of PT. Indonesia Villa Jaya, with questionnaire collection methods and census sampling techniques, and data analysis techniques with descriptive analysis. The results of this study indicate that the use of information technology for knowledge sharing at PT Indonesia Villa Jaya is at a good level. ICT Infrastructure has the highest value for information technology variables that support knowledge sharing.